Urbanisation Through Brick Kilns: The Interrelationship Between Appropriation of Nature and Labour Regimes. (May 2020) - Mishra, Pratik
This article follows the emergence and growth of a brick kiln cluster in Khanda village on the periphery of the Delhi's National Capital Region agglomeration. Khanda's landscape and ecology have been profoundly altered and shaped by brick kilns in what can be taken as a manifestation of extended urbanisation. This urbanisation is not only bound up with the urban demand for bricks but is also mediated by various situated processes that are not city-centred. The article draws attention to a number of these processes—Khanda's history of agrarian decline as a condition of possibility for the kiln cluster, the upscaled metabolism of the soil with changing forms of commodification and the emergence of new labour processes that alter as well as reproduce historical relations of production particular to brick kilns. The article establishes dialogue between the fields of agrarian urbanism and urban political ecology to develop a situated critique of the metabolism of brick kilns. It also brings brick kilns into Marxist debates on the interrelationship between nature and labour within capitalist production through a discussion on the changing modes of appropriation of soil and its relation to everyday practices of working the soil.